Potential benefits of immunomodulator use with vedolizumab for maintenance of remission in ulcerative colitis. Issue 1 (7th September 2021) - Naganuma, Makoto; Watanabe, Kenji; Motoya, Satoshi; Ogata, Haruhiko; Matsui, Toshiyuki; Suzuki, Yasuo; Ursos, Lyann; Sakamoto, Shigeru; Shikamura, Mitsuhiro; Hori, Tetsuharu; Fernandez, Jovelle; Watanabe, Mamoru; et al.
Abstract: Background and Aim: This study aimed to determine the efficacy and safety of vedolizumab treatment with or without concomitant immunomodulator use in Japanese patients with moderate‐to‐severe ulcerative colitis. Methods: Among enrolled patients in a phase 3 study conducted in Japan (clinicaltrials.gov, NCT02039505), data from patients allocated to 300‐mg intravenous vedolizumab for induction and maintenance phases were used for this exploratory analysis. Efficacy endpoints were clinical response, clinical remission, and mucosal healing at week 10 and clinical remission and mucosal healing at week 60, and disease worsening and treatment failure during the maintenance phase. Results: At week 10, the differences in clinical response, clinical remission, and mucosal healing rates between the subgroups (those with concomitant immunomodulator use minus those without) were 0.7 (95% confidence interval: −14.3, 15.7), 3.3 (95% confidence interval: −8.5, 15.2), and 1.8 (95% confidence interval: −13.0, 16.5), respectively. At week 60, the differences in clinical remission and mucosal healing between the subgroups with and without concomitant immunomodulator use were 26.1 (95% confidence interval: −3.5, 55.6) and 29.9 (95% confidence interval: 1.4, 58.4), respectively. The proportions of patients without treatment failure at day 330 of the maintenance phase were 90.7% with concomitant immunomodulator use and 73.7% without. No marked differences in incidence of infections were observed between subgroups. Conclusions: This study suggested the possibility that concomitant immunomodulator use may be beneficial to maintain the clinical efficacy of vedolizumab.